Penerapan Metode SAW untuk Pemilihan Siswa Terbaik pada SMPN 266 Jakarta Berbasis Web - Afnan Dwi Astuti; Khairunnisa Fadhilla Ramdhania; Dani Yusuf (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
In this study, the author aims to build a website-based decision support system for selecting the best student at SMPN 266 Jakarta. For this reason, the selection of the best students not only has good academic scores, but can be supported by non-academic scores. In the process of determining the best students at SMP Negeri 266 Jakarta, it is still done manually using only report cards, so that the data processing process can take a long time and there is a risk of errors in the assessment process. The method that the author uses is the Simple Additive Weighting (SAW) method, the concept of the SAW method is to determine the weight value for each attribute, then proceed with a ranking process to determine the best alternative. There are four criteria that the author uses, namely Mid-Semester Assessment (PTS), Final Semester Assessment (PAS), Extracurricular and Attendance. The use of a Decision Support System (DSS) is expected to assist decisions made in selecting and determining who is the best student, considering that so far it has not used a certain method in selecting students, so that sometimes decisions are considered less precise and effective. The system is made using Hypertext Preprocessor (PHP) as a programming language with a MySQL database. The final result obtained, this system can produce output in the form of a report on the list of the best prospective students along with the value calculated using the SAW method.